Activation of Sphalerite by Ammoniacal Copper Solution in Froth Flotation - Xian Xie; Kai Hou; Bo Yang; Xiong Tong (Journal of Chemistry)
The activation of sphalerite particles by ammoniacal copper solution (ACS) was investigated in this study. This microflotation study was conducted on a single sphalerite mineral with the particles size of 38 μm to 75 μm. Results showed that ACS has somewhat better activation effect than copper sulphate (a traditional activator) with sodium isobutyl xanthate as the collector. Agglomeration observation, contact angle measurement, and X-ray photoelectron spectroscopy measurement results of sphalerite particles verified the superiority of this new activator. Therefore, the substitution of copper sulphate with ACS would increase the separation efficiency not only in marmatite flotation but also in sphalerite flotation.